2010
DOI: 10.1007/s11095-010-0252-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dosing Schedule on Organ Exposure to Cyclosporin in Pediatric Hematopoietic Stem Cell Transplantation: Analysis with a PBPK Model

Abstract: CI may be slightly more favorable than II for aGVHD prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(33 reference statements)
0
10
1
1
Order By: Relevance
“…As a consequence, administration of cyclosporin by II or CI may have equal efficacies, provided that the average blood concentration achieved is similar. The higher AUC of receptor occupancy in the interstitial fluid of aGVHD target organs yielded by CI, compared to II in our previous study (9), does not result in increased efficacy, probably because the difference in receptor occupancy is too small. As AUC is equal to the product of average concentration and dosing interval, AUC 0-24 h may also be used as a predictor of efficacy.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…As a consequence, administration of cyclosporin by II or CI may have equal efficacies, provided that the average blood concentration achieved is similar. The higher AUC of receptor occupancy in the interstitial fluid of aGVHD target organs yielded by CI, compared to II in our previous study (9), does not result in increased efficacy, probably because the difference in receptor occupancy is too small. As AUC is equal to the product of average concentration and dosing interval, AUC 0-24 h may also be used as a predictor of efficacy.…”
Section: Discussioncontrasting
confidence: 55%
“…The pediatric physiologically based pharmacokinetic (PBPK) model, including 11 organs validated in children (9), was fitted individually to the venous whole-blood cyclosporin concentrations of the 61 pediatric patients undergoing HSCT and receiving only cyclosporin as immunosuppressive treatment. For each patient, the data records included the dosing history, the first two concentration measurements, body weight, age, and hematocrit.…”
Section: Pbpk Model In Pediatric Patients and Predicted Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Gérard et al recently showed that intermittent infusions (i.e., a 2 h infusion administered every 12 h) had higher simulated cyclosporine concentrations in the GVHD target organs but lower simulated cyclosporine concentrations in the kidney, suggesting that intermittent infusions would be superior. 158 …”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%